2008
DOI: 10.3899/jrheum.080333
|View full text |Cite
|
Sign up to set email alerts
|

MAGE-B2 Autoantibody: A New Biomarker for Pediatric Systemic Lupus Erythematosus

Abstract: Objective-Melanoma-associated antigen gene B2 (MAGE-B2) encodes an embryonic antigen normally silenced after birth except in testis and placenta. We identified the MAGE-B2 gene and autoantibodies in pediatric patients with systemic lupus erythematosus (SLE) glomerulonephritis. Our purpose herein was to determine the prevalence of MAGE-B2 autoantibodies in association with active SLE, as well as to infer a pathogenetic role of MAGE-B2 protein through its distribution in cells and tissues.Methods-A cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Literature search reveals quite a number of cross-sectional studies on the relationship between novel biomarkers and activity of lupus nephritis [ 13 , 63 – 69 , 73 78 ]. These are summarized in Table 1 (serum biomarkers) and Table 2 (urine biomarkers).…”
Section: Biomarkers Correlating With Lupus Renal Activity In Crossmentioning
confidence: 99%
“…Literature search reveals quite a number of cross-sectional studies on the relationship between novel biomarkers and activity of lupus nephritis [ 13 , 63 – 69 , 73 78 ]. These are summarized in Table 1 (serum biomarkers) and Table 2 (urine biomarkers).…”
Section: Biomarkers Correlating With Lupus Renal Activity In Crossmentioning
confidence: 99%
“…Another recently described autoantibody with possible clinical relevance in pediatric lupus is directed against the melanomaassociated antigen gene (MAGE)-B2. Seventeen of forty pediatric lupus patients had autoantibodies to MAGE-B2 as compared to only two of twenty-three adult controls [19]. Disease activity and active nephritis were higher in MAGE-B2-positive versus MAGE-B2-negative patients [19].…”
Section: Autoantibodiesmentioning
confidence: 95%
“…Several proteins and miRs regulate G3BP1 at the post-transcriptional level. Many of these proteins interact with 5'-untranslated region (5'-UTR) (Hoftman et al, 2008;Lee et al, 2020;Somasekharan et al, 2015) of G3BP1, than with 3'-untranslated region (3'-UTR) (Deng et al, 2015;Liu et al, 2021;Lv et al, 2017). In contrast, many miRs have been identified to bind the 3'-UTR of G3BP1 and subsequently downregulate its expression.…”
Section: Regulation Of G3bps At Transcriptional Translational and Pos...mentioning
confidence: 99%
“…Thus, YB-1 regulates G3BP1 availability for SG assembly (Zhang et al, 2019a) and there is a strong association between YB-1 and G3BP1 expression in human sarcomas (Somasekharan et al, 2015). Lee and colleagues showed that Melanoma-associated antigen gene B2 (MAGE-B2), which is normally found in testicular tissue but is abnormally expressed in tumors (Hoftman et al, 2008), can interact with the 5′-UTR of G3BP1. This interaction results in increased translation of G3BP1 (Lee et al, 2020).…”
Section: Regulation Of G3bps At Transcriptional Translational and Pos...mentioning
confidence: 99%